Nuestras tiranías. Tocqueville acerca del despotismo democrático - González de Requena, Juan Antonio (2013)
“Our Tyrannies. Tocqueville on Democratic Despotism”. Although the lexicon of “tyranny” and “despotism” is subject to historical changes in meaning, we still keep on using those terms to refer to some types of illegitimate, unjust or indecent political regimes. So does Tocqueville, when he describes the new ways of despotism emerging from modern democratic revolution. In this article, we explore the uses of “tyranny” and “despotism” in Tocqueville’s thought, and we also try to discover the concrete models or social prototypes which could inspire Tocqueville’s prognosis concerning a tutelary democratic despotism.